Biomineralization Biotechnology Utilizing Lysinibacillus sphaericus to Improve Mechanical Properties of Mortar - Ridwan Syarif; Siti Khodijah Chaerun; Ridho Kresna Wattimena (HAYATI Journal of Biosciences, 2024)
Biomineralization has notably enhanced the qualities of cement-based materials, particularly through bacterial-facilitated calcite precipitation via calcium lactate oxidation. However, existing research mainly targets self-healing aspects, with little focus on bio-based mortar properties. Consequently, this study provides a comprehensive examination of the enhancements in dry density, ultrasonic pulse velocity (UPV), and flexural strength, achieved through the application of a novel indigenous bacterial strain (Lysinibacillus sphaericus strain SKC/VA-1) from Indonesia, coupled with the incorporation of calcium lactate pentahydrate as an additive. A total of six mortar samples were prepared to investigate the influence of bacteria on the properties of mortar through biomineralization. The samples included plain mortar (M), mortar mixed with calcium lactate pentahydrate (ML), mortar mixed with a 10% v/v bacterial inoculum (MB1), mortar mixed with calcium lactate pentahydrate and a 10% v/v bacterial inoculum (MLB1), mortar mixed with a 20% v/v bacterial inoculum (MB2), and mortar mixed with calcium lactate pentahydrate and a 20% v/v bacterial inoculum (MLB2). The employment of a distinct bacterial strain for oxidizing calcium lactate represents an innovative aspect of the current study. The presence of organic calcium was found to have no adverse effects on the mortar matrix. Optimal inoculum concentrations of bacteria (10% v/v), in conjunction with calcium lactate pentahydrate, yielded superior mechanical properties. Mineralogical characterization via X-ray diffraction and microstructural analysis through scanning electron microscopy substantiated the incidence of calcite precipitation, which facilitated pore infilling and consequently augmented both the ultrasonic pulse velocity and the flexural strength of the mortar.